Secondary School Libraries in Bangladesh: A Proposed National Strategy for Rejuvenating Secondary School Library Services - Monirul Islam, M.; Abdullah-Al-Mahmud (Journal of Information and Knowledge, 2020)
Secondary school library plays a significant role to support the school course curriculum. However, national policy or strategy for secondary school library is yet to be formulated in Bangladesh. The present study made an effort to propose a strategy for secondary school library in Bangladesh, to review and re-envision its functions and services. This strategy will act as a guideline for a librarian and secondary school authorities. Based on the present status of secondary school library in Bangladesh, the present study also focuses on the significance, organizational structure, obstacles and possible outcomes of this strategy.